Automated radiosynthesis of the adenosine A2A receptor‐targeting radiotracer [18F]FLUDA. (24th March 2022) - Lai, Thu Hang; Wenzel, Barbara; Moldovan, Rareş‐Petru; Brust, Peter; Kopka, Klaus; Teodoro, Rodrigo
Abstract : [ 18 F]FLUDA is a selective radiotracer for in vivo imaging of the adenosine A2A receptor (A2A R) by positron emission tomography (PET). Promising preclinical results obtained by neuroimaging of mice and piglets suggest the translation of [ 18 F]FLUDA to human PET studies. Thus, we report herein a remotely controlled automated radiosynthesis of [ 18 F]FLUDA using a GE TRACERlab FX2 N radiosynthesizer. The radiotracer was obtained by a one‐pot two‐step radiofluorination procedure with a radiochemical yield of 9±1%, a radiochemical purity of ≥99%, and molar activities in the range of 69–333 GBq/μmol at the end of synthesis within a total synthesis time of approx. 95 min ( n  = 16). Altogether, we successfully established a reliable and reproducible procedure for the automated production of [ 18 F]FLUDA. Abstract : [ 18 F]FLUDA is a selective radiotracer for in vivo imaging of the adenosine A2A receptor (A2A R) by positron emission tomography (PET). We report herein a remotely controlled automated radiosynthesis of [ 18 F]FLUDA using a GE TRACERlab FX2 N radiosynthesizer. The radiotracer was obtained by a one‐pot two‐step radiofluorination procedure (radiochemical yield: 9 ± 1%, radiochemical purity: ≥99%, molar activities: 69–333 GBq/µmol (EOS), total synthesis time: approx. 95 min). Altogether, we successfully established a reliable and reproducible procedure for the automated production of [ 18 F]FLUDA .